Isolation and screening of plant growth promoting bacteria (PGPB) from rice (Oryza sativa) and rhizosphere soil - อุบลรัตน์, จริยา; มูลมั่งมี, สมพร; คุณจักร, นงพงา; มูลมั่งมี, ดวงทิพย์ (Progress in Applied Science and Technology, 2018)
This study was to isolate and screen growth promoting bacteria from root, stem of rice and rhizosphere soil samples. The totally 478 bacterial isolates was isolated and screened for phosphate (P) and zinc (Zn) solubilizing activities using tricalcium phosphate (Ca3(PO4)2) and zinc oxide (ZnO) as the substrates. The results showed that the isolate AS10-1 and AR9-1 were the best of P and Zn solubilizing strains. They had solubilizing clear zone index of 1.85 and 3.43 respectively. When compared to the reference strains of Gluconacetobacter azotocaptans BCC 36449 and G. diazotrophicus BCC 20215, indicating that the reference strains exhibited P solubilizing clear zone index of 1.81 and 1.16, and Zn solubilizing clear zone index of 2.38 and 2.57 respectively, which lower than the isolated strains in this study. Screening of 41 effective bacterial isolates capable of both P and Zn solubilization for indole acetic acid production was performed and also indirect nitrogen fixation was measured by Nessler’s method. It was found that the isolate AB6-3 was the highest of Indole-3-acetic acid production with the yield of 58.25 µg/ml. It was interested that this isolate produced 3 and 4.5 times higher than that of two reference strains, respectively. The isolate NB3-3 was found to be the best nitrogen fixing activity. Identification of all 41 plant growth promoting bacteria was done using 16S rRNA gene sequencing. They were classified into 8 genera as of Gluconacetobacter sp., Cosenzaea sp., Nguyenibacter sp., Serratia sp., Ochrobactrum sp., Asaia sp., Bukholderia sp. and Pseudomanas sp.